2012
DOI: 10.1177/0960327112450902
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adenovirus Ad-RUNrf2 reduces paraquat-induced A549 injury

Abstract: Ad-RUNrf2 adenovirus was successfully constructed and can be stably expressed and regulated in cells. Ad-RUNrf2 can reduce PQ-induced inflammation, oxidative stress and apoptosis in A549 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Previous studies have revealed that SIRT1 promotes the activity of NRF2 and upregulates the expression of NRF2 downstream genes, such as SOD (14,15), and that the knockdown of SIRT1 results in the downregulation of NRF2 expression (16). In our previous SIRT1 exerts protective effects against paraquat-induced injury in mouse type II alveolar epithelial cells by deacetylating NRF2 in vitro study, we confirmed that NRF2 is activated and plays a role in protecting A549 lung cells against oxidative damage following exposure to PQ (17). However, the association between SIRT1 and NRF2, as well as their effects on PQ-induced oxidative stress remain to be elucidated.…”
Section: Introductionsupporting
confidence: 80%
“…Previous studies have revealed that SIRT1 promotes the activity of NRF2 and upregulates the expression of NRF2 downstream genes, such as SOD (14,15), and that the knockdown of SIRT1 results in the downregulation of NRF2 expression (16). In our previous SIRT1 exerts protective effects against paraquat-induced injury in mouse type II alveolar epithelial cells by deacetylating NRF2 in vitro study, we confirmed that NRF2 is activated and plays a role in protecting A549 lung cells against oxidative damage following exposure to PQ (17). However, the association between SIRT1 and NRF2, as well as their effects on PQ-induced oxidative stress remain to be elucidated.…”
Section: Introductionsupporting
confidence: 80%
“…As shown in our previous study, an anti-IL-6 receptor antibody and an NF- κB inhibitor, caffeic acid phenethyl ester, reduce the titers of the A/H1N1 pdm 2009 virus [15]. Furthermore, IL-6 activates caspases [16] that enhance the release of viral ribonucleoprotein complexes from the nucleus [17]. In our previous study, a caspase-3 inhibitor, Z-DEVD-fmk, reduced the A/H1N1 pdm 2009 viral titers in the supernatants [15].…”
Section: Discussionmentioning
confidence: 57%
“…Studies [18] have also shown that PQ poisoning can induce the release of inflammatory cytokines in human alveolar epithelial A549 cells, with increased expression of TNF- α , IL-1 β , and IL-6. In this study, a rat model of acute lung injury was constructed by PQ exposure.…”
Section: Discussionmentioning
confidence: 99%